The shadows of the past: how implicit institutions influence entrepreneurship - Stefan Bauernschuster; Oliver Falck; Robert Gold; Stephan Heblich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper investigates the impact of implicit institutions on the decision to become an entrepreneur. Implicit institutions are here defined as mindsets that have developed as the result of norms and traditions and we expect they will have an influence on risk attitudes and opportunity recognition. We conduct a natural experiment based on Germany’s recent history and compare individuals born and raised in the former socialist East Germany (GDR) with their West Germany (FRG) counterparts. Our analysis confirms the expected difference in values between individuals from East and West Germany and also shows that these differences influence the probability of being self-employed. In the process of our analysis, we also sketch the ongoing economical transition process in East Germany, which severely disturbs a proper analysis of the institutional differences from a macro-perspective.
Keywords: L26; A13; P39; 330; Implicit Institutions; Entrepreneurship; Socialism; Capitalism; Unternehmer; Selbstständige; Berufswahl; Soziale Werte; Institutionelle Infrastruktur; Übergangswirtschaft; Neue Bundesländer; Vergleich; Alte Bundesländer; Deutschland